ANALISIS KIMIA BATUAN BASEMEN GRANITOID DI SUB CEKUNGAN JAMBI, SUMATRA SELATAN BERDASARKAN DATA DARI SUMUR JSB-3, JSB-4 DAN JSB-6 - -, Euis Tintin Yuningsih (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Research area located at Jambi sub basin, the northern part of South Sumatra Basin formed during Tertiary. The propose of the research is to determine petrological characteristics of pre-Tertiary basement rock based on major oxides analysis from the granitoid basement rock in research area with AAS method (Atomic Absorption Spectrophotometry) so the petrogenesis could be determined including kinds and characteristics of parent magma. Chemical rock analysis confirm the lithology of granitoid basement in Jambi sub basin are intermediate – acid magmas, calc-alkaline, medium – high K, metalluminous, subduction-related (orogen) at active continental margin. Granitoid at JSB-4 and JSB-6 shows magnetite series and I type. This Mesozoic granitoid probably as extension from the Thailand and Burma granite province, that underline the fact that there has been a history of subduction-related magmatism along Southwestern edge of Sundaland since earliest Mesozoic times.